Effect of eccentric exercise on markers of muscle damage in patients with chronic obstructive pulmonary disease. (3rd July 2021) - Mujaddadi, Aqsa; Moiz, Jamal Ali; Singla, Deepika; Naqvi, Irshad Hussain; Ali, Mir Shad; Talwar, Deepak
ABSTRACT: Background : Eccentric exercise may be considered as an attractive alternative to conventional exercise in pulmonary rehabilitation (PR) for patients with chronic obstructive pulmonary disease (COPD). However, due to muscle damage associated with eccentric exercise, there has been reluctance in using this exercise form in PR. Objective : The aim of the present study was to investigate the effect of eccentric exercise on markers of muscle damage in patients with COPD. Methods : We analyzed 14 patients with moderate-severe COPD and 14 age-matched healthy controls. Both groups performed submaximal eccentric exercise of the elbow flexors. Muscle soreness (MS), maximum voluntary isometric contraction (MVC) of the elbow flexors, elbow range of motion (ROM), upper arm circumference (CIR), and biochemical markers such as creatine Kinase (CK) and lactate Dehydrogenase (LDH) were measured at pre-exercise, 24 h, 48 h, and 72 h following submaximal eccentric exercise. Results : There was a significant difference in markers of muscle damage, MS ( p = .002), MVC ( p < .001), ROM ( p = .010), CIR ( p < .001), and LDH ( p = .001). However, no significant differences were observed in the activity of CK ( p = .261) between COPD and control group following eccentric exercise which indicates greater degree of muscle damage in COPD as compared with control. Conclusion : Sub-maximal eccentric exercise causes significantly greater muscle damage in elderly COPD patients than healthy controls. Therefore, initial exercise should be progressed with lower intensities to prevent undue muscle damage in these patients.